PARTISIPASI KHALAYAK MEDIA ONLINE TERHADAP LIPTAN6.COM DALAM MEMENANGKAN PERSAINGAN INDUSTRI MEDIA MASSA DI INDONESIA - Bayquni Bayquni (Universitas Prof. Dr. Moestopo (Beragama), 2018)
Background of this research is new media or also called online media, researchers want to do an analysis of how Liputan6.com can do media convergence in accordance with market needs, so liputan6.com can win the competition in New Media or New Media industry. By looking at the formulation of the problem, it will be seen how the convergence in online media is done. The results of research on Liputan6.com stated that. In conducting Convergence Liputan6.com converges on the economy, on social and on culture, which further directs its preaching to young people. In addition, Liputan6.com also participates in the creation of affiliate program packaging, expression, collaboration of probleme solving and conection. By engaging the audience with a term called citizen journalism, so the audience to believe that what is conveyed contains elements of truth, and the last Commodification is Sibernat where the limitations of space and time become lost when directed and packaged in accordance with the purpose of Liputan6.com in informing the news. The results of research on Liputan6.com can be concluded that Liputan6.com has fulfilled the element in doing cultural participation in order to capture the competition of new media industry.